ECONOMIC GROWTH AND MILITARY EXPENDITURE NEXUS: EMPIRICAL EVIDENCE FROM ASEAN-10 ECONOMIES - Saudi, Nur Surayya Mohd; Asmanur, Othman (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
This study aims to test the causal relationship between military expenditure and economic growth in ASEAN-10 using time-series data covering the period from 1960 to 2023. It revisits existing evidence on the ASEAN-10 economies with updated data on the effects of military expenditure on economic growth. Empirical analysis was conducted using cointegration analysis and causality tests to justify the relationship and direction of causality between the variables. The findings reveal a positive long-run relationship and a unidirectional long-run causality from economic growth to military expenditure in most ASEAN-10 countries.The finding that economic growth drives military expenditure in these countries is significant, as it suggests that defence spending is economically sustainable when aligned with national income. As countries grow wealthier, they gain greater fiscal capacity to invest in security without compromising development priorities. The empirical results support the case for a sustainable defence budget, efficient resource allocation, and expanded opportunities for domestic defence industry development ultimately contributing to long-term economic resilience and self-reliance.